Pengaruh Literasi Digital Terhadap Hasil Belajar Ekonomi Di Era Pandemik Covid-19 Siswa Kelas XI SMA Negeri 6 Kota Tangerang Selatan - Musyarofatul Qudsiyah; Enok Nurhasanah (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
This study aims to determine the Effect of Digital Literacy on Economic Learning Outcomes in the Era of the Covid-19 Pandemic for Class XI Students at SMA Negeri 6 Tangerang Selatan City. The research methodology used is the associative method with a quantitative research approach. The population that the researcher uses is all students of SMA Negeri 6 Tangerang Selatan City using the Rendom Sampling technique by determining the number of samples using the Slovin formula and obtained as many as 114 students with an error rate of 5%. The data collection instruments used were Economic Daily Examination (UH) documents and questionnaires. Prerequisite test of analysis using normality test and linearity test with data analysis technique used is simple regression analysis with the help of IMB SPSS Statistic 22 program.The results showed that digital literacy had a fairly low influence on economic learning outcomes in the pandemic era with 24.2% results which gave changes to the digital literacy variable, while 75.8% was influenced by other variables that were not found in this study.